2014
DOI: 10.1088/1009-0630/16/1/09
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Copper Nanoparticles Using Dielectric Barrier Discharge at Atmospheric Pressure and its Mechanism

Abstract: Dielectric barrier discharge (DBD) cold plasma at atmospheric pressure was used for preparation of copper nanoparticles by reduction of copper oxide (CuO). Power X-ray diffraction (XRD) was used to characterize the structure of the copper oxide samples treated by DBD plasma. Influences of H2 content and the treating time on the reduction of copper oxide by DBD plasma were investigated. The results show that the reduction ratio of copper oxide was increased initially and then decreased with increasing H2 conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Among different techniques, non-thermal plasma reduction of copper oxides demonstrates promising results [4][5][6][7][8][9]. As it was shown in our previous research [9], few nanometer-thick native oxide layers were almost completely removed from copper surfaces within 20 s of treatment using a dielectric barrier discharge (DBD) plasma in an Ar/H 2 gas at 100 hPa.…”
Section: Introductionmentioning
confidence: 80%
“…Among different techniques, non-thermal plasma reduction of copper oxides demonstrates promising results [4][5][6][7][8][9]. As it was shown in our previous research [9], few nanometer-thick native oxide layers were almost completely removed from copper surfaces within 20 s of treatment using a dielectric barrier discharge (DBD) plasma in an Ar/H 2 gas at 100 hPa.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, it is technically feasible to keep the gas temperature of AP cold plasma at low temperatures. For example, the gas temperature for plate‐to‐plate DBD cold plasma is about 200 °C after 15 min stabilizing time . In addition, to limit the gas temperature, the treatment for plate‐to‐plate DBD cold plasma was generally not continuously operated.…”
Section: Reduction Mechanism Of Ap Cold Plasmamentioning
confidence: 99%
“…The results showed that no copper NPs can be detected without adding H 2 gas into the cold plasma, and the highest reduction rate of copper oxide was achieved at 20%H 2 content. The optical emission spectra indicated that copper oxide was not reduced by excited‐state hydrogen atoms or heating effect, and excited‐state hydrogen molecules and hydrogen radicals were proposed to be the reducing agents . Hydrogen radicals were also deemed to be the reducing agents when using sonochemical deposition method and hot‐wire method for metal ions reduction.…”
Section: Reduction Mechanism Of Ap Cold Plasmamentioning
confidence: 99%
“…Xu Zhijian et al have investigated the use of dielectric barrier discharges fed with hydrogen (H 2 ) to reduce copper oxide and obtain Cu-NPs (~35 nm in diameter). 21 Masaaki Nagatsu et al investigated an Ar/H 2 radio-frequency (RF) microplasma with a copper wire sacrificial electrode (1 mm diameter) showing the possibility of producing nanostructured copper thin films. 22 Another study by G. Dinescu et al was carried out with an argon RF microplasma jet without hydrogen, also with a sacrificial copper electrode (a copper cylinder in this case).…”
Section: Introductionmentioning
confidence: 99%